PENGARUH LEVERAGE, RETURN ON INVESTMENT (ROI), RETURN ON EQUITY (ROE), COST OF CAPITAL (COC) TERHADAP INVESTASI ASING LANGSUNG PADA MULTINATIONAL CORPORATION YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sofyan Halim (Universitas Mercu Buana, 2017)
This study aims to examine and examine the effects of leverage, return on investment, return on equity and cost of capital on foreign direct investment in multinational corporations listed on the Indonesia Stock Exchange. By using a causal method with the aim to test the hypothesis about the effect of leverage, ROA, ROE and cost of capital to foreign direct investment. In addition, it aims to examine the relationship between variables that are symmetrical, with a sample of 66 PMA companies listed on the Indonesia Stock Exchange. Based on result of hypothesis test of research get result that Laverage, Return On Investment, Return On Equity and Cost Of Capital have no effect to foreign direct investment, in this case is portion of foreign stock at PMA company that researched